The Effect of Red Okra Fruit Extract (Abelmoschus esculentus) on Lactobacillus acidophilus Growth - Firdha Muharraran; Idamawati Nababan; Syafira Rizka Mutia Lubis (HM Publisher, 2023)
Background: Dental caries occupies the top rank of dental and oral diseases that many Indonesians complain about. Dental caries is caused by Lactobacillus acidophilus. One of the latest treatments for caries disorders is by giving mouthwash. Mouthwash currently circulating, almost all contain chlorhexidine as the main ingredient. However, there are side effects from using chlorhexidine for a long period of time, namely discoloration of the teeth, which cannot be removed simply by brushing the teeth. Red okra fruit contains flavonoids which are useful as antibacterial. This study aimed to determine the potential of red okra fruit extract (Abelmoschus esculentus) as an antibacterial against Lactobacillus acidophilus in vitro. Methods: In vitro experimental studies. A total of 28 petri dishes contained bacterial cultures of Lactobacillus acidophilus grouped into 7 groups consisting of 2 control groups and 5 treatment groups of red okra fruit extract concentration of 10% -50%. Inhibition zone diameter analysis was carried out with the help of SPSS software using univariate and bivariate methods. Results: The group that received chlorhexidine showed the highest ability to produce the largest diameter of the inhibition zone compared to all treatment groups. Along with increasing the dose of red okra fruit extract, the ability of okra fruit extract to increase in producing a larger diameter of the inhibition zone. Conclusion: Red okra fruit extract shows effectiveness as an antibacterial Lactobacillus acidophilus and increases the extract's concentration.